Mechanisms contributing to the differential haemodynamic effects of bombesin and cholecystokinin in conscious, Long Evans rats. - Janssen, P. J. (1991)
1. Long Evans rats were chronically instrumented with intravascular catheters and pulsed Doppler probes to assess changes in renal, mesenteric and hindquarters blood flows and vascular conductances in response to bombesin (2.5 micrograms kg-1, i.v.) and cholecystokinin (CCK) (0.5 and 5.0 micrograms kg-1, i.v.). 2. Bombesin caused an increase in heart rate and blood pressure, together with a transient renal vasoconstriction and prolonged mesenteric vasodilatation; there was an early hindquarters vasodilatation followed by vasoconstriction. 3. In the presence of phentolamine, bombesin caused a fall in blood pressure due to enhanced hindquarters vasodilatation; these effects were reversed by propranolol and hence were possibly due to circulating adrenaline acting on vasodilator beta 2-adrenoceptors. 4. During concurrent administration of phentolamine, propranolol and atropine, bombesin caused prolonged tachycardia and a rise in blood pressure. The renal vasoconstrictor and mesenteric vasodilator effects of bombesin were not reduced under these conditions and thus probably were direct and/or indirect non-adrenergic, non-cholinergic (NANC) effects. 5. CCK caused dose-dependent increases in blood pressure accompanied by renal, mesenteric and hindquarters vasoconstriction followed, after the higher dose, by vasodilatations. The lower dose of CCK increased heart rate but there was a bradycardia followed by a tachycardia after the higher dose. 6. Experiments with antagonists as described above indicated the pressor effect of CCK was mediated largely through alpha-adrenoceptors, as were the mesenteric and hindquarters vasoconstrictor effects; CCK exerted NANC negative chronotropic effects. 7. All the effects of CCK were markedly inhibited by L364,718. This observation, and the finding that L364,718 had no effect on the responses to bombesin, together with the dissimilarities in the regional haemodynamic effects of exogenous CCK and bombesin, indicate that the cardiovascular actions of the latter were not dependent on the release of endogenous CCK.